Especialities of translation the articles from japanese language to kazakh language - Saudanbekova, Sh.; Tundebayeva А. (Journal of Oriental Studies, 2016)
this article describes the features of the Japanese translation of the article to the Kazakh language. based on the research the author of the peculiarities of the translation process that can be used in the translation of article journalistic style.